Analisis Pengaruh Akuntabilitas dan Transparansi Terhadap Kinerja Anggaran dengan Konsep Value For Money Padarsud Djoelham Binjai - Yuni Shara; Debbi Chyntia Ovami; Rindhira Humairah (Journal of Trends Economics and Accounting Research, 2020)
The objective of this research was to determine (1) The Effect of Accountability on Budget Performance with the Concept of Value for Money at Djoelham Binjai Regional Hospital, (2) The Effect of Transparency on Budget Performance with the Concept of Value for Money at Djoelham Binjai Regional Hospital, (3) The Effect of Accountability and Transparency on Budget Performance with the Concept of Value for Money at Djoelham Binjai Regional Hospital. This research design was to use quantitative methods. The sample was selected through a purposive sampling method, namely 69 employees at Djeolham Binjai Regional Hospital. The data collection technique used a questionnaire. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple regression analysis and hypothesis testing. The results showed that (1) Accountability had a positive and significant effect on budget performance with the concept of value for money at Djoelham Binjai Hospital, (2) Transparency had no significant effect on budget performance with the concept of value for money. at Djoelham Binjai Hospital, (3) Simultaneously accountability and transparency had a positive and significant effect on budget performance with the concept of value for money at Djoelham Binjai Regional Hospital.